REALISING THE INCLUSION OF YOUNG PERSONS WITH DISABILITIES IN POLITICAL AND PUBLIC LIFE IN KENYA (African Disability Rights Yearbook, 2021)
Voting is central to citizenship. It is mainly through political participation that the voices of persons with disabilities are amplified and their rights implemented. However, more than being a tool of empowerment and agency, voting is a marker of dignity; those deprived of the franchise not only feel disempowered but dishonoured. The Kenyan Constitution seeks to radically overhaul the exclusion experienced by minorities and marginalised groups, including the youth and persons with disabilities. Notably, article 54(2) requires the progressive implementation of the principle that at least 5 per cent of all elective and appointive positions are held by persons with disabilities. This article assesses constitutional and legislative provisions on participation in political and public life by young persons with disabilities. It also reviews the measures proposed by the Persons with Disabilities Bill 2015 to realise the inclusion of youth in public life. It further proposes to take advantage of the broad wording of article 54(2) of the Constitution which, unlike the gender rule, does not limit the state to specific measures of implementation. This provision, therefore, offers wide latitude in the approaches that may be used to secure greater inclusion in public life of young persons with disabilities. Among other measures, strategic litigation seeking creative remedies, such as a compelling mandamus (which has been effective in securing socio-economic rights), might provide the impetus needed to ensure greater inclusion of young persons with disabilities in all spheres of public life in Kenya.
Keywords: political participation; voting; Kenyan Constitution; constitutional and legislative provisions; young persons with disabilities